Adaville Enterprise : iclap Switch / Izzat Danial Norman ...[et al.] - Norman, Izzat Danial; Zahari, Aiman Helni; Abdull Manan, Muhammad Aminuddin; Mohd Rashdan, Anis Suhaila; Zakaria, Nor Amira Azwa (2017)
iClap switch is a basic electronics mini project, made with the help of the basic components. iClap Switch has the ability to turn ON/OFF any electrical component or circuit by the clap sound.